Ezekiel At the Turn of the Century - Kohn, Risa Levitt (Currents in biblical research, 2003)
Recent scholarship has helped illuminate historical circumstances sur rounding the Israelite Exile. As a result, the book of Ezekiel has gained renewed interest. As a prophet of the Exile, Ezekiel is recognized as an important and liminal figure in the evolution of Israelite theology. In the 1994 volume of Currents, Pfisterer Darr surveyed the state of the field of Ezekiel studies. The present article identifies and examines several emerg ing trends in Ezekiel scholarship since the publication of Pfisterer Darr's study, including literary relations in Ezekiel, the psychology of the prophet, Ezekiel's sign-acts, adulterous Jerusalem (Ezek. 16; 23), corporate and indi vidual responsibility (Ezek. 18), and recent scholarship on Ezek. 40-48.